Experimental and finite element analysis of tensile properties of oil palm trunk im-pregnated with epoxy - Nik Wan, F.; Abubakar, A.; Suriani, M.J.; Saat, A.M.; Fitriadhy, A.; Wan Nik, W.M.N.; Abdul Majid, M.S.; Mukhtar, Z.Z.; Ilyas, R.A.; Mohd Nurazzi, N.; Norrrahim, M.N.F. (Institute of Physics, 2024)
This research focuses on determining the elastic properties from the development of a three-dimensional constitutive model of impregnated oil palm trunk reinforced with epoxy (OPTE) composite. The research aims to simulate the tensile behaviour of OPTE composite for finite element analysis and compared with the OPTE experimental results, respectively. The OPTE composites were manufactured by using one of the vacuum infusion techniques namely the vacuum-assisted resin transfer moulding technique. In this research, OPTE composite is considered as a unidirectional fibre due to the wood board in the resin. Tensile tests were conducted to provide the material properties as inputs into three-dimensional constitutive model. The tensile test was performed according to ASTM D3039. The test was divided into three zones including zone I (outer), zone II (middle) and zone III (inner). The three elastic constants (elastic modulus, shear modulus and Poisson's ratio) of material properties were obtained from the tensile test data and theoretical equation. The model was developed in Abaqus software. The results from finite element method (FEM) were compared with the experimental results. There was a good agreement and promising results between FEM and the experimental data.